Estudos sobre liberação controlada e vetorização de drogas através de lipossomas - Gomes de Oliveira, Anselmo [UNESP]; Cardillo, José Augusto; Scarpa, Maria Virgínia [UNESP]; Wanczinski, Bruna Juliana [UNESP]; Da Silva Jr., Arnóbio Antônio [UNESP] (My University, 2005)
The text highlights the state of research related with the application of liposomes in the control of drug delivery and drug target to infectious diseases. Liposomes have several pharmaceutical applications and this manuscript is primarily focused on the potential of this colloidal system as an antibiotic carrier system and of administration through several accesses via to organism. Numerous case studies in which liposomes have successfully been used to improve pharmacological drug effect are presented. Mechanisms involved in drug delivery, application possibilities, research and development and efforts to reach these objectives are discussed. © Copyright Moreira Jr. Editora. Todos os direitos reservados.
Studies on the controlled drug delivery and drug targeting through liposomes
Keywords: Antibiotics; Drug delivery control; Drug target; Liposomes; Prolonged delivery; drug carrier; liposome; colloid; controlled drug release; drug delivery system; drug effect; drug mechanism; drug research; drug targeting; human; infection; review